ANALISIS BAURAN PEMASARAN DENGAN MINAT KUNJUNGAN ULANG PASIEN POLIKLINIK SPESIALIS RUMAH SAKIT PERTAMINA RANTAU TAHUN 2023 - Marpaung, Juli Fitria (Jurnal Inovasi Kesehatan Masyarakat, 2024)
This research aims to look at the relationship between the marketing mix based on aspects of service quality, price, promotion and location and to analyze the most dominant factors that have a relationship with interest in repeat visits by patients at the specialist polyclinic at Pertamina Rantau Hospital in 2023. This type of research is quantitative correlation, with cross sectional research design, aims to identify the relationship between independent and dependent variables in quantitative data. This method explores the relationships between variables, using systematic analysis to develop mathematical models, theories and hypotheses related to the phenomenon. The sample that will be used in this research is 97 patients from the specialist polyclinic at Pertamina Rantau Hospital in 2023. The research shows that although the level of marketing mix relationship is based on aspects of service quality, promotion and location with the patient's interest in repeat visits at the Specialist Polyclinic at Pertamina Rantau Hospital in 2023 2023 is low, there is a significant relationship in each of these aspects. The level of relationship based on the price aspect is moderate, with a significant relationship as well. The most dominant factor that has a relationship with patients' intention to revisit is price.